(untitled) (CAHIERS MAGELLANES-NS, 2024)
Customer relationship management is defined as “a comprehensive strategy and process of acquiring, retaining and partnering with selective customers to create superior value for the company and the customers” (Parvatiyar and Sheth, 2001). It aims at efficiently and effectively increasing the acquisition and to retain the potential customers by maintaining appropriate relationships with them in the long-run (Payne and Frow, 2006). Today customer has many options to choose from a wide array of products and companies offering them. Implementations of best CRM practices has resulted lower operational costs and higher growth of revenue to the company. Effective and innovative use of CRM boosts customer satisfaction as well as retention rates (Reichheld et al). In light of the above premise this study aims to understand the theoretical foundations of research in CRM with a special reference to the retail industry. The study further is structured with a detailed survey of literature on customer relationship management. The third section talks about the theoretical background. Forth section discusses the role of customer relationship management in the retail sector. Finally, this report concludes with the discussion of future scope of this study.